Portuguese healthcare reforms in the context of crisis: external pressure or domestic choice? - Asensio, M.; Popic, T. (Social Policy and Administration, 2019)
As a result of the recent economic crisis, in 2011 Portugal signed a Memorandum of Understanding with the European Central Bank, the European Commission and the International Monetary Fund (the 'Troika'). In exchange for Troika's financial assistance, the Memorandum required the implementation of a specific set of reforms targeted at the healthcare sector. The literature on policy reforms in the context of crisis and conditionality argues that governments have little room to maneuver in responding to external pressure. We challenge this view, finding that even in cases of conditionality and strong external pressures, crisis can be used as a window of opportunity for reforms substantially shaped by domestic policy choices. In the case of Portuguese health reforms, these choices aimed on resolving country-specific deficiencies of the healthcare system and were enabled by the two main political parties' strategies of tacit cooperation and blame avoidance. The article emphasizes the need for more fine-grained analysis of welfare reforms in the crisis affected countries that pays equal attention to the institutional characteristics and to the political context and strategies.